Design and characterization of multijunction and non-standard photodetectors as colour sensors - Chen, Zhiying (Nanyang Technological University, 2023)
In the information era, sensors are everywhere. And a high-performance sensor is critical for the development of the Internet of Things. Humans need many kinds of sensors to detect the signals around them from nature. Especially, the information of light is one of the most important signals from nature. And the colour is the most common property of light. In common life, we usually distinguish things based on their colour, so the colour detection of the smart device is a vital capability to achieve artificial intelligence. Furthermore, colour detection is able to be used in phototelegraphy. Therefore, high-performance colour sensor is popular among researchers all over the world. Nowadays, there are many types of colour sensors, such as JFET colour sensors, CMOS colour sensors, CCD imagers and so on. However, because of the Moore’s Law, the devices in the ICs are necessary to scale down. Thanks to the capability to detect three colours simultaneously, a multijunction colour sensor is an excellent choice. For detection accuracy, it is important to achieve balanced three-colour detection. That is also the goal of this dissertation project. Due to the process compatibility, excellent detection accuracy and the trend of the device’s scaling down, the Si-based multijunction colour sensor is a comparable device for colour sensing. In this dissertation project, a multijunction colour sensor is designed, which has a balanced simultaneous three-colour detection. Firstly, MATLAB calculation is used to figure out the basic structure parameters. After that, based on those structure parameters, the dopant concentration of each layer is determined. To design the fabrication processes, Tsuprem4 is used to simulate the fabrication of the multijunction colour sensor. And the process conditions are confirmed. Using Medici, the electrical and optical properties of the multijunction colour sensor are characterized. Finally, verifying the TCAD simulation results, the design of the multijunction colour sensor can operate as proposed. And the light detection function is satisfied with our design and calculation.